Anticancer applications of phytochemicals in gastric cancer: Effects and molecular mechanism - Liang, Zhaofeng; Xu, Yumeng; Zhang, Yue; Zhang, Xinyi; Song, Jiajia; Qian, Hui; Jin, Jianhua (Frontiers in Pharmacology, 2023)
Gastric cancer is the fourth most common malignant cancer and is a life-threatening disease worldwide. Phytochemicals has been shown to be a rational, safe, non-toxic, and very promising approach to the prevention and treatment of cancer. It has been found that phytochemicals have protective effects against gastric cancer through inhibiting cell proliferation, inducing apoptosis and autophagy, suppress cell invasion and migration, anti-angiogenesis, inhibit Helicobacter pylori infection, regulate microenvironment. In recent years, the role of phytochemicals in the occurrence, development, drug resistance and prognosis of gastric cancer has attracted more and more attention. In order to better understand the relationship between phytochemicals and gastric cancer, we briefly summarize the roles and functions of phytochemicals in gastric cancer tumorigenesis, development and prognosis. This review will probably help guide the public to prevent the occurrence and development of gastric cancer through phytochemicals, and develop functional foods or drugs for the prevention and treatment of gastric cancer.